2022
DOI: 10.4038/kjm.v11i1.7648
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Career Indecision among Management Undergraduates in Sri Lanka

Abstract: The main purpose of this study is to identify the significant factors affecting career indecision in light of state university management undergraduates in Sri Lanka. In the light of literature, five independent variables namely self-efficacy, parental influences, the economic condition of the country, poverty level and career counselling facilities were identified. The sample was derived from 153 final year management students from two metropolitan and two rural state universities. Self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Zin, M. S. Jaafar [22], looked at the data and concluded that the university employment process is not to be seen as a onetime event. It must be seen as an ongoing procedure.…”
Section: Ventura G G and Bringula Pr [20]mentioning
confidence: 99%
“…Zin, M. S. Jaafar [22], looked at the data and concluded that the university employment process is not to be seen as a onetime event. It must be seen as an ongoing procedure.…”
Section: Ventura G G and Bringula Pr [20]mentioning
confidence: 99%